Pengaruh Pendidikan Politik dan Efikasi Politik Terhadap Peningkatan Partisipasi Politik Peserta Kegiatan Fasilitasi Badan Kesbangpol Provinsi Sumatera Barat - Noor Ramadhian, Fajar; Asrinaldi, Asrinaldi; Zetra, Aidinil (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study examines the influence of political education on political participation, which is mediated by political efficacy. This study focuses on the forms of political participation according to the theory of Samuel P. Huntington and Joan M. Nelson. The approach used is quantitative with a survey method. The research sample of 400 respondents was selected by simple random sampling. Data were analyzed using path analysis techniques with the help of the SPSS program version 24. The results of the study show: First, political education and political efficacy simultaneously contribute 47% to political participation, while the remaining 53% is influenced by other variables not studied. The average level of political participation after the political education facilitation activities is classified as high, with a mean value of 3.74 (equivalent to 74.80%). Second, the results of this study recommend ongoing political education efforts to strengthen democratic involvement in society. Third, it is important for the West Sumatra Provincial Kesbangpol Agency to pay attention to the subject of political education implemented from the aspects of age, education level,monthly income, and other social characteristics.